Volatility Spillover of World Oil Prices on the Rupiah Exchange Rate: Evidence from a Net Oil-Importing Emerging Economy - Aulia Keiko Hubbansyah; Iha Haryani Hatta; Safitri Siswono; Arya Jati Kusuma Al-Ansori (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2026)
Crude oil price volatility is a first-order source of macroeconomic risk for net oil-importing emerging economies, transmitting through the exchange rate to inflation, fiscal balances, and financial stability. Indonesia’s transition since 2004 from a net oil exporter to a net oil importer has fundamentally altered this exposure, yet systematic empirical evidence quantifying the resulting transmission mechanism remains limited. This study examines volatility spillovers between world oil prices and the Indonesian rupiah exchange rate over 1990-2024, employing a two-stage framework combining ARCH-GARCH volatility extraction with a generalized VAR spillover-index approach incorporating generalized forecast error variance decomposition (FEVD) and rolling-window estimation. The results reveal a pronounced and asymmetric spillover structure: 26.79% of rupiah exchange rate forecast error variance is attributable to shocks originating in the global oil market, compared to only 5.85% in the reverse direction. The net spillover of +20.94 percentage points confirms that global oil markets operate as a dominant net transmitter of volatility, while the rupiah functions as a persistent net receiver; the Total Connectedness Index (TCI) of 32.6% indicates substantive interdependence between the two markets. Rolling-window analysis further reveals that spillover intensity is strongly state-dependent, amplifying during five major global shock episodes: the 1997-1998 Asian financial crisis, the 2004-2008 oil boom, the 2008-2009 global financial crisis, the 2014-2016 oil price collapse, and the 2020 COVID-19 pandemic. These findings carry concrete implications for Bank Indonesia’s exchange rate surveillance, fiscal subsidy stress-testing, and energy diversification policy.